2012
DOI: 10.1016/j.ejpn.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Visual expertise in paediatric neurology

Abstract: Clinicians of varying expertise analyse patient video cases differently. Clinical teachers should take these differences into account when optimising educational formats with patient video cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 24 publications
(34 reference statements)
1
48
0
Order By: Relevance
“…For example, in a classic study on chick sexing, experts knew exactly which information was relevant for determining the sex of day-old chicks, leading to the ability to sex 98% of the chicks correct at a rate of 1000 chicks per hour, while novices did not know which information to use for discrimination between male and female chicks (Biederman & Shiffrar, 1987). In the medical domain, Balslev and colleagues found that pediatricians looked more often to task-relevant body parts (showing abnormal movements) rather than task-irrelevant body parts (showing no abnormal movements) in videos of infants having epileptic seizures, compared to medical students (Balslev et al, 2011).…”
Section: Comparison Learning For Real-life Complex Visual Tasksmentioning
confidence: 94%
“…For example, in a classic study on chick sexing, experts knew exactly which information was relevant for determining the sex of day-old chicks, leading to the ability to sex 98% of the chicks correct at a rate of 1000 chicks per hour, while novices did not know which information to use for discrimination between male and female chicks (Biederman & Shiffrar, 1987). In the medical domain, Balslev and colleagues found that pediatricians looked more often to task-relevant body parts (showing abnormal movements) rather than task-irrelevant body parts (showing no abnormal movements) in videos of infants having epileptic seizures, compared to medical students (Balslev et al, 2011).…”
Section: Comparison Learning For Real-life Complex Visual Tasksmentioning
confidence: 94%
“…Unlike other experiments, which have contrasted experts and naïve observers [11][12][13], this is the first, to the authors' knowledge, to compare the effect of varying clinical information on visual search behaviour in radiology. In this experiment, one of the clinical conditions suggested a low expectation of abnormality (visa application), one suggested a high expectation (previous cancer) and one gave no clinical information at all suggesting an unknown expectation of abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…Verbal data, such as think-aloud data, 1 are most commonly collected together with eye-tracking data to answer this question.(e.g. 19,21,22 ) Furthermore, performance data are often a useful addition to eyetracking data. In the example of the student working with the virtual patient, retrospective thinking aloud can provide information about why the virtual tutor helped the student to find the relevant information.…”
Section: Pupil Diameter Over Timementioning
confidence: 99%
“…Theories of diagnostic reasoning suggest that less experienced students will have trouble distinguishing relevant from irrelevant information.(e.g. 19 ) How can these students be helped? Research in visual expertise shows that 'percentage of time spent on relevant information' is a measure that could be useful for investigating this phenomenon.…”
Section: Pupil Diameter Over Timementioning
confidence: 99%